Mitochondrial Alternative Oxidase Is Not a Critical Component of Plant Viral Resistance But May Play a Role in the Hypersensitive Response - Ordog, Sandi H. (American Society of Plant Physiologists, 2002)
Transgenic tobacco (Nicotiana tabacum) with altered levels of mitochondrial alternative oxidase (AOX) were used to examine the potential role of this electron transport chain protein in resistance to tobacco mosaic virus. We examined the effect of AOX expression on the salicylic acid-induced resistance in susceptible plants and the resistance responses of plants harboring the N-gene. A lack of AOX did not compromise the ability of salicylic acid treatment to heighten the resistance of susceptible plants. In plants with the N-gene, a lack of AOX did not compromise the ability of the hypersensitive response to restrict the virus or the ability of the plant to develop systemic acquired resistance. Overexpression of AOX did not heighten the resistance of susceptible plants, but did result in smaller hypersensitive response lesions, suggesting a link between mitochondrial function and this programmed cell death event. We conclude that AOX is not a critical component of the previously characterized salicylhydroxamic acid-sensitive pathway important in viral resistance.